Impact of CSR-relevant news on stock prices of companies listed in the Austrian Traded Index (ATX) - Manuela Ender; Finn Brinckmann (International Journal of Financial Studies, 2019)
This paper examines the short-term influence of CSR-relevant news on the enterprise value in the form of respective shareholder value, which is represented by the corresponding stock price. This effect is measured using an event study applied to companies in the 'Austrian Traded Index' (ATX). Subsequently, the results of the study show that CSR-relevant news in the financial portal finanzen.net trigger statistically significant abnormal returns and average cumulated abnormal returns within a period of five days. Based on these research results, it is stated that CSR-relevant news has a significant impact on the shareholder value of a company represented by its stock price. The hypotheses defined on the basis of the previously conducted studies on this topic were only partially confirmed. In particular, the negative effects of negative CSR-relevant news are insufficiently shown. Based on these findings, it can be deduced that the effects of the news are reinforced by the CSR relevance, although media presence due to the publications is a factor to be explored.
Keywords: G14; G32; Q56; 330; corporate social responsibility; CSR-relevant news; event study; Austrian Traded Index